Modeling and performance simulation of a gas cooler for a CO2 heat pump system - Chang, Young-Soo; Kim, Min Seok (TAYLOR & FRANCIS INC, 2007)
The outlet temperature of a gas cooler has a great effect on the efficiency of carbon dioxide heat pump systems. In order to obtain a small approach temperature difference at the gas cooler, a near-counterflow type heat exchanger has been proposed, and a larger heat transfer area is demanded. Therefore, the optimum design for gas coolers involving the analysis of trade-offs between heat transfer performance and cost is desirable. For this study, a simulation model has been developed for fin-and-tube type gas coolers, and an air-side heat transfer correlation is proposed. The developed model was confirmed by experimental results. The effects of geometric parameters, such as transverse tube spacing, longitudinal tube spacing, number of tube rows, and fin spacing, on the performance of heat exchangers were investigated using the developed model. This study suggests various simulation results for optimum design of gas coolers.